Methodological Challenges Human Capital Assessment Faces and the Return on Investment Put Into It - Dulevski, Lalko (Research Papers, 2009)
In the studies are considered essential methodological issues of human capital assessment and the return of the investments in it. On the basis of an overview of the main approaches for human capital assessment, primary attention is given to the income-based approach corresponding with the author’s concept for market determination of human capital. Through the use of sufficient representative information base, human capital assessments in Bulgarian are implemented in different socio- economic aspects. Special attention is given to the possibility for application and development of the theoretical model for the investment effectiveness in higher education. On the basis of the applied approaches are brought out some challenges to the human capital in the country and the return of the investments.